2021
DOI: 10.3390/brainsci11101268
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Intervention Strategies Directed to Speech and Language Deficits in Primary Progressive Aphasia: Practice-Based Evidence from 18 Cases

Abstract: Background: Practice-based evidence can inform and support clinical decision making. Case-report series about the implementation of programs in real-world clinical settings may contribute to verifying the effectiveness of interventions for treating PPA in specific contexts, as well as illustrating challenges that need to be overcome. Objective: To describe and provide practice-based evidence on the effectiveness of four cognitive rehabilitation programs designed for individuals with PPA and directed to speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 78 publications
1
12
0
4
Order By: Relevance
“…Statistically significant clinical benefits were observed in 13 individuals, while for five, the results were maintained. However, generalization to untrained items or to other tasks were observed only in two individuals 91 .…”
Section: Treatment Of Primary Progressive Aphasiasmentioning
confidence: 86%
See 1 more Smart Citation
“…Statistically significant clinical benefits were observed in 13 individuals, while for five, the results were maintained. However, generalization to untrained items or to other tasks were observed only in two individuals 91 .…”
Section: Treatment Of Primary Progressive Aphasiasmentioning
confidence: 86%
“…Dement Neuropsychol 2022 September;16(3 Suppl. 1): [83][84][85][86][87][88][89][90][91][92][93][94][95] In current clinical practice, memantine is commonly added to ChEI in subjects with moderate or severe vascular dementia. However, the benefits of memantine are very limited or controversial for controlling cognitive and neuropsychiatric symptoms, as well as for slowing cognitive or functional decline 61 .…”
Section: Chei and Memantinementioning
confidence: 99%
“…Benefícios clínicos estatisticamente significativos foram observados em 13 indivíduos, enquanto para cinco, os resultados foram mantidos. No entanto, a generalização para itens não treinados ou para outras tarefas foi observada apenas em dois indivíduos 91 .…”
Section: Tratamento Da Demência Frontotemporal Variante Comportamentalunclassified
“…In "Cognitive Intervention Strategies Directed to Speech and Language Deficits in Primary Progressive Aphasia: Practice-Based Evidence from 18 Cases" [10], the authors demonstrated the importance of symptom-targeted intervention in a group of patients with PPA, again with heterogeneous clinical presentations. While there was no control cohort or within-group comparison to determine the impact of alternative treatment ap-proaches, the patients showed improved performance in trained items at post-test, with an individualized focus on either naming, sentence production, motor speech functioning, or phonological functioning.…”
Section: Treatmentmentioning
confidence: 99%